The impact of hypothermic pulsatile machine perfusion versus static cold storage: A donor-matched paired analysis in a scenario of high incidence of delayed kidney graft function - de Sandes-Freitas, Tainá Veras (2020)
Background: Material/Methods: Results: Conclusions: The present study analyzed the impact of hypothermic pulsatile machine perfusion (MP) following a long period of static cold (SC) storage in the peculiar Brazilian scenario of high incidence of delayed graft function (DGF), despite good donor characteristics. A retrospective analysis, with a 1-year follow-up, of 206 recipients of donor-matched paired kidneys was per-formed. Of the 206 donor kidneys, 103 were maintained exclusively in static cold storage (SC group) and 103 were kept on machine perfusion after a period of SC preservation (MP group). All donors were brain dead. Only 4.9% of the kidneys were from expanded-criteria donors. Static cold ischemia time (CIT) in the SC group was 20.8±4.1 hours vs. 15.8±6.2 hours in the MP group (P<0.001). Dynamic CIT in the MP group was 12.3±5.7 hours. MP significantly reduced DGF incidence (29.1% vs. 55.3%, P<0.001), and this effect was confirmed in multivariable analysis (OR, 1.115; 95% CI, 1.033–1.204, P=0.001). No differences were observed between the groups with regard to DGF duration, length of hospital stay, incidence of primary nonfunction and acute rejec-tion, graft loss, death, or renal function. In this Brazilian setting, MP following a long period of SC preservation was associated with reduced DGF incidence in comparison with SC storage without MP.